Efficacy of increased dose of rupatadine up to 20 mg on itching in Japanese patients due to chronic spontaneous urticaria, dermatitis, or pruritus: A post hoc analysis of phase III clinical trial. Issue 5 (23rd August 2019) - Hide, Michihiro; Suzuki, Takamasa; Tanaka, Ayaka; Aoki, Hiroshi
Abstract: Objectives: The effect of rupatadine, a novel H1 antihistamine with platelet‐activating factor antagonist activity, had been demonstrated for itching in Japanese patients with chronic spontaneous urticaria, dermatitis, or pruritus in a 12‐month, open‐label clinical trial (JapicCTI‐152787). However, patients could have received an updose at various timings due to distinct reasons in the study; timing of updose was not evaluated. This study aimed to elucidate the relationship between performance of rupatadine and timing of updose. Methods: For 206 enrolled patients was evaluated the total pruritus score (TPS) to Week 2 with 10 mg rupatadine. From Week 3 to Week 52, rupatadine was updosed to 20 mg accordingly. Subpopulation was categorized by absence/presence of updosing and timing of updose (Week 3 or ≥Week 5). Results: Reduction of TPS from baseline to Week 2 in patients updosed at Week 3 was significantly lower than those given an updose at ≥Week 5 and fixed dose. However, significant improvement in the change in mean TPS from 1 week pre‐updose to the second week post‐updose was achieved regardless of updose timing, scoring −0.903 for Week 3 and −0.983 for ≥Week 5 ( P  < 0.001). Conclusions: The results inferred the inclusivity of patients who either updosed during the earlier phase due to lack of efficacy, or later due to aggravation of symptoms. The results of this subgroup analysis produced evidence of appropriateness for using 10 mg rupatadine as the starting dose, and evaluating the necessity of updose to 20 mg during the first 2 weeks for nonresponsive patients. Abstract : Rupatadine is a novel second‐generation antihistamine with platelet‐activating factor antagonist activity. Updosing to 20 mg was efficacious in Japanese patients with insufficient response with 10 mg or patients who experienced aggravation of symptoms. The subgroup analysis on the total pruritus score over time by timing of updose produced evidence that the updose regimen is appropriate in clinical setting.